The Value of Proximity to Water in Residential Areas - Jan Rouwendal; Ramona van Marwijk; Or Levkovich (Tinbergen Institute, 2014)
Proximity to water is appreciated by households. Hedonic analyses that try to measure the value of this amenity are potentially biased by omitted variables as locations close to the water may be selected by households with higher incomes who construct more luxury houses. Since it is difficult to observe all relevant characteristics, the coefficient for proximity to water may be biased upwards. We circumvent this problem by exploiting a specific characteristic of the Dutch system of planned residential development: often a number of identical houses are constructed close to each other. By comparing the values of such identical houses, we can measure the effect of proximity to water under almost ideal circumstances. The results show a significant impact of this amenity, but of a smaller magnitude than was suggested by many earlier studies, thereby confirming the conjectured presence of omitted variable bias.
Keywords: D12; D61; R21; 330; hedonic analysis; local amenities; ommited variable bias